Outcomes of a Pharmacist-Led Hepatitis C Virus Treatment Program in an Urban Safety-Net Health System, Chicago, 2017-2019. (July 2022) - Hunt, Bijou R.; Cetrone, Hollyn; Sam, Sharon; Glick, Nancy R.
Objective: A recommendation in March 2020 to expand hepatitis C virus (HCV) screening to all adults in the United States will likely increase the need for HCV treatment programs and guidance on how to provide this service for diverse populations. We evaluated a pharmacist-led HCV treatment program within a routine screening program in an urban safety-net health system in Chicago, Illinois. Methods: We collected data on all patient treatment applications submitted from January 1, 2017, through June 30, 2019, and assessed outcomes of and patient retention in the treatment cascade. Results: During the study period, 203 HCV treatment applications were submitted for 187 patients (>1 application could be submitted per patient): 49% (n = 91) were aged 55-64, 62% (n = 116) were male, 67% (n = 125) were Black, and 15% (n = 28) were Hispanic. Of the 203 HCV treatment applications, 87% (n = 176) of patients were approved for treatment, 91% (n = 161) of whom completed treatment. Of the 161 patients who completed treatment, 81% (n = 131) attended their sustained virologic response (SVR) follow-up visit, 98% (n = 129) of whom reached SVR. The largest drop in the treatment cascade was the 19% decline from receipt of treatment to SVR follow-up visit. Conclusion: The pharmacist-led model for HCV treatment was effective in navigating patients through the treatment cascade and achieving SVR. Widespread implementation of pharmacist-led HCV treatment models may help to hasten progress toward 2030 HCV elimination goals.